Hyaluronic acid-based bioink improves the differentiation and network formation of neural progenitor cells - Pereira, Inês; Lopez-Martinez, Maria J.; Villasante, Aranzazu; Introna, Clelia; Tornero, Daniel; Canals, Josep M.; Samitier, Josep (Frontiers in Bioengineering and Biotechnology, 2023)
Three-dimensional (3D) bioprinting is a promising technique for the development of neuronal in vitro models because it controls the deposition of materials and cells. Finding a biomaterial that supports neural differentiation in vitro while ensuring compatibility with the technique of 3D bioprinting of a self-standing construct is a challenge. In this study, gelatin methacryloyl (GelMA), methacrylated alginate (AlgMA), and hyaluronic acid (HA) were examined by exploiting their biocompatibility and tunable mechanical properties to create a suitable material for printing neural progenitor cells (NPCs) and supporting their long-term differentiation. This composite biomaterial presented the desired physical properties to mimic the extracellular matrix of the brain with high water intake, low stiffness, and slow degradation while allowing the printing of defined structures. NPCs were printed and differentiated for up to 15 days, and cell viability and neuronal differentiation markers were assessed throughout the culture. The viability rates were maintained at approximately 80% at all time points. However, the levels of β-III tubulin marker increased over time, demonstrating the compatibility of this biomaterial with neuronal cell culture and differentiation. Furthermore, these cells showed increased maturation with corresponding functional properties, which was also demonstrated by the formation of a neuronal network that was observed by recording spontaneous activity via Ca2+ imaging.